Synthesis and characterization of a novel ambipolar polymer semiconductor based on a fumaronitrile core as an electron‐withdrawing group. Issue 5 (5th December 2012) - Jeong, Hyung‐Gu; Khim, Dongyoon; Jung, Eunhwan; Yun, Jin‐Mun; Kim, Juhwan; Ku, Jamin; Jang, Yun Hee; Kim, Dong‐Yu
Abstract Two conjugated polymers containing stilbene and fumaronitrile moieties were synthesized to investigate their electronic properties by the existence of electron‐withdrawing cyano groups on a vinylene backbone. The cyclic voltammetry investigation and time‐dependent density functional theory calculations indicated that the cyano substituents lowered the lowest unoccupied molecular orbital (LUMO) energy level by about 0.65 and 0.63 eV, respectively. The lowering of the LUMO energy levels due to the electron‐withdrawing properties of the cyano substituents could enhance electron injection capability. Furthermore, bithiophene‐fumaronitrile (donor‐acceptor) intermolecular interaction facilitates the self‐assembly of the polymer chains. Organic field‐effect transistors (OFETs) based on PBTSB without the electron‐withdrawing group only exhibit hole transport, while OFETs based on PBTFN with cyano substituents exhibit ambipolar characteristics. The growth of PBTFN crystalline fibrils was observed with increasing annealing temperature, which enhanced hole and electron mobility. A complementary‐like inverter using PBTFN with ambipolar properties exhibited good symmetry with an inverting voltage nearly half that of the power supply with a gain of 9 at VDD = 100 V. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013